Применение интеллектуальной диагностической инфраструктуры для управления кибербезопасностью. Часть 2. Поддержка жизненного цикла системы киберзащиты - Мирошник, М. А.; Крылова, Виктория Анатольевна; Демичев, А. И. (Український державний університет залізничного транспорту, 2016)
Кибербезопасность в условиях глобальной информатизации общества рассматривается сегодня как одна из основных компонент национальной безопасности. В работе рассматривается подход к разработке и использованию систем киберзащиты, основанный на выделении интеллектуальной надстройки над традиционными механизмами защиты и построении единой унифицированной среды для создания и поддержки функционирования систем защиты. Представляются отдельные механизмы управления кибербезопасностью.

How use of structural features in the construction of hybrid models allows supporting of models adjustment and adaptation to problem-subject environment was considered in the article. The following features were attributed to structural ones: the type of learning algorithm; kind of activation function; the number of layers of the neural network; type of neurons; way of spreading information in neural networks; method of evaluating and interpreting the results of the neural network; the format of fuzzy inference rules; fuzzification and defuzzification method; way to implement the operations of fuzzy implication and logical operations NOT, AND, OR; kind of used genetic operators and the target functions, etc. We propose to use a neural network approach as a basis for the decision of difficulty tasks using decisionsupport systems. Its effectiveness can be enhanced by: prior training or adjustment of individual neural modules for solvable problem; incorporation of knowledge about the peculiarities of the domain in the hierarchical (multilayer) neural networks structure; application of basic types of hybrid models in which neural network communicates with other information technologies.
Keywords: распределенные сети; сеть; доступ; аутентификация; шифрование; защита информации; базы данных; модели безопасности; methods of diagnosis; monitoring; complex failures; computer information management systems; distributed networks; network protocols; network attacks; routed service; authentication; encryption; data protection; database security model